Engineering More Stable, Selectable Marker-Free Autoluminescent Mycobacteria by One Step - Yang, Feng (PLoS One, 2015)
In our previous study, we demonstrated that the use of the autoluminescent Mycobacterium tuberculosis as a reporter strain had the potential to drastically reduce the time, effort, animals and costs consumed in evaluation of the activities of drugs and vaccines in live mice. However, the strains were relatively unstable and lost reporter with time without selection. The kanamycin selection marker used wasn’t the best choice as it provides resistance to amino glycosides which are an important class of second line drugs used in tuberculosis treatment. In addition, the marker could limit utility of the strains for screening of new potential drugs or evaluating drug combinations for tuberculosis treatment. Limited selection marker genes for mycobacterial genetic manipulation is a major drawback for such a marker-containing strain in many research fields. Therefore, selectable marker-free, more stable autoluminescent mycobacteria are highly needed. After trying several strategies, we created such mycobacterial strains successfully by using an integrative vector and removing both the resistance maker and integrase genes by Xer site-specific recombination in one step. The corresponding plasmid vectors developed in this study could be very convenient in constructing other selectable marker-free, more stable reporter mycobacteria with diverse applications.